2017
DOI: 10.1111/pde.13327
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric severity of alopecia tool

Abstract: The Severity of Alopecia Tool serves as a tool for alopecia research and a clinical guideline for following progression of disease. The original Severity of Alopecia Tool score does not take into account pediatric age groups. As new clinical trials for alopecia areata include more children, a more accurate tool should be available for this population. By collecting images from patients 2-21 years of age and aligning the hair-bearing regions of the scalp, we created an adaptation of the Severity of Alopecia Too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Treatment failure was defined as inadequate regrowth or cessation of MTX due to adverse events. Current existing scoring systems for AA (SALT I, SALT II) were not used in the present study as they were not designed for paediatric alopecia assessments and have not been validated in the paediatric setting …”
Section: Methodsmentioning
confidence: 99%
“…Treatment failure was defined as inadequate regrowth or cessation of MTX due to adverse events. Current existing scoring systems for AA (SALT I, SALT II) were not used in the present study as they were not designed for paediatric alopecia assessments and have not been validated in the paediatric setting …”
Section: Methodsmentioning
confidence: 99%
“…A previous study showed that children aged <12 have a percentage difference in the hair-bearing scalp from adults and concluded that children aged 2–11 years need a pediatric SALT scoring system. However, in the current manual SALT scoring method, a change of 2% might not affect the overall SALT score 16 .…”
Section: Discussionmentioning
confidence: 96%
“…Of this set, 1484 images were taken from 293 participants seen within the dermatology clinics of the Children’s Hospital of Philadelphia and the Hospital of the University of Pennsylvania (Penn) (Table). Scalp images were captured and standardized following guidelines defined by the SALT score and its pediatric adaptation: for each participant, up to 4 views of the head (top, back, and lateral) were taken per time point. For the alopecia top scores analysis and automation, we added an additional 121 top (crown) view only images from 111 participants enrolled via Penn Dermatology’s alopecia monitoring interface, Trichy (Figure 2).…”
Section: Methodsmentioning
confidence: 99%